Rickettsial pathogens circulating in urban districts of Rio de Janeiro, without report of human Brazilian Spotted Fever - Campos, Sabrina Destri Emmerick; Cunha, Nathalie Costa da; Machado, Camila de Souza Cerqueira; Telleria, Erich Loza; Cordeiro, Matheus Dias; Fonseca, Adivaldo Henrique da; Toma, Helena Keiko; Santos, Jefferson Pereira Caldas Dos; Almosny, Nádia Regina Pereira (Revista brasileira de parasitologia veterinaria, 2020)
Spotted fever group rickettsioses are emerging diseases. In some of these diseases, domestic dogs act as sentinels. Canine serological studies have demonstrated that rickettsial dispersion is concentrated in rural areas, seroprevalence being higher where human rickettsioses are endemic. In Rio de Janeiro, the Atlantic forest vegetation has been devastated by urbanization. In this context, we aimed to detect Rickettsia spp. in urban areas of the West Zone of Rio de Janeiro. Sera from 130 dogs were tested by Indirect Immunofluorescence Assay, and ticks collected from these dogs were tested by polymerase chain reaction. We found the rate of serological reactions against R. rickettsii and R. parkeri in our study area to exceed those of rural and non-endemic areas, highlighting the importance of dogs as urban sentinels. The possibility of contact with opossums and capybaras increased the chances of exposure to Rickettsia spp., reinforcing the hypothetical link between the landscape and the rickettsial wild cycle. Rhipicephalus sanguineus sensu lato was the tick most frequently observed. PCR-positive samples showed similarity with R. rickettsii and R. felis, an emerging pathogen rarely reported from ticks. We observed that rickettsiae circulate in urban places and ticks from indoor environments, which may be involved in bacterial epidemiology.
Keywords: Rhipicephalus sanguineus; lidé; Rickettsia Infections; nemoci psů; horečka Skalistých hor; Brazil; Brazílie; rickettsiové infekce; Humans; psi; séroepidemiologické studie; zvířata; Ticks; Dogs; Animals; klíšťata; Seroepidemiologic Studies; Rocky Mountain Spotted Fever; Rickettsia; Dog Diseases